AN ANALYSIS OF READING COMPREHENSION OF FUNCTIONAL TEXT AT EIGHTH GRADE SMP KASIH LESTARI TEMBILAHAN - Budianto; Maizarah; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2021)
This research was conducted based on the problems found during the teaching and learning process in class VIII of SMP Kasih Lestari Tembilahan, specifically about students' understanding of the functional text. The problem found is that 50% of the students cannot understand the text they are reading, they cannot reach the KKM score, and Functional text is one of the texts in which students must be able to read and comprehend. This research is included in quantitative descriptive research. The population of this research is class VIII SMP Kasih Lestari Academic Year 2020/2021. The population and sample of this study were 23 people who were taken using the total sampling technique. The instrument used was an objective test. Data from students' objective tests are analyzed based on indicators and then interpreted and become research findings. Based on the results of the study showed that students of class VIII SMP Kasih Lestari: 1. The ability of reading comprehension in Main Idea Aspect showed at the poor level of 10 people out of 23 students (30,4%). 2. The reading comprehension ability in Reference Aspect showed at enough level of 10 people out of 23 students (43,4%). 3. The reading comprehension ability in Inference Aspect showed at the excellent level of 15 people out of 23 students (65,2%). 4. The ability of reading comprehension in Unfamiliar Word Aspect showed at the poor level of 15 people out of 23 students (34,7%). 5. The ability of reading comprehension in Factual Information Aspect showed at enough level of 5 people out of 23 students (43,4%). From the above research results, it can be concluded that students still experience many difficulties in reading comprehension, especially in functional texts by applicable rules. Furthermore, based on the results of this study, teachers are expected to be able to provide better teaching techniques, and students can do more exercises to improve students' reading comprehension abilities.